All about joints : a maintenance guide - Siegel, Irwin M., 1927-2019 (DEMOS, 2002)
From the acclaimed author of All About Bone and All About Muscle , All About Joints tells you everything you might want to know about your joints, how they work, how they can be injured, illnesses to which they are prone, and how to keep them healthy. The book is written for the intelligent reader who wants to better understand normal functioning of the musculoskeletal system and the injuries and ailments to which it is subject. It covers practical matters such as proper exercise and sports, the prevention and treatment of injury, arthritis and other ailments that affect our joints, and much m.